A Graphical Method for Design of Cantilevered and Suspended Span Beams - Mehta, Purushottam B. (Engineering Journal, 1981)
Cantilevered and suspended span beams are widely used in industrial building roof construction, particularly in single story structures, where joist spacing and beam spans are equal. This type of construction can save a considerable amount of structural steel and reduce erection time. According to the National Building Code of Canada, beams should be designed for loading conditions which produce maximum stresses. For continuous beam framing alternate span loading produces maximum moments. To minimize work in determining maximum beam moments and length of cantilevers, the author has prepared charts which, for specific loading conditions, can give coefficients for moment and cantilever length.